Stages of Organizing Research Activity in Students - Muradova Zulfia Kayumovna (Genius Journals, 2023)
In this article, the author highlighted the ability to develop students' inner desire to acquire knowledge, to develop independence and activity, to be interested in practical activities, to strive for a goal, and to act freely
Keywords: research; competence; innovation; intellectual